AB0281 SAFETY AND RETENTION RATE AFTER SWITCHING FROM ETANERCEPT ORIGINATOR (ETN) TO ETANERCEPT BIOSIMILAR (SB4) IN INFLAMMATORY JOINT DISEASES: DATA FROM REAL LIFE. (2nd June 2020) - Bruni, C.; Gentileschi, S.; Capassoni, M.; Pacini, G.; Bardelli, M.; Baldi, C.; Tofani, L.; Cometi, L.; Nacci, F.; Bartoli, F.; Fiori, G.; Cantarini, L.; et al.
Abstract : Background: SB4 in now commonly used in the treatment of inflammatory joint diseases, with evidence of efficacy and persistence up to 12 months from switching in both randomized controlled trials in Rheumatoid Arthritis (RA), Psoriatic Arthritis (PsA) and Ankylosing Spondylitis (AS). Objectives: we investigated the safety and retention rate of SB4 at 6, 12 and 18 months after switching from ETN in two rheumatology departments in our region. Methods: adult patients with RA, PsA, AS, Juvenile Idiopathic Arthritis (JIA) and other rheumatic diseases treated with ETN for at least 6 months, switched to SB4 in stable clinical conditions, were eligible for this retrospective evaluation. Data on adverse events (in particular infectious events), loss of efficacy (articular, cutaneous, ocular or intestinal disease re-activation) and persistence on treatment were collected since latest available follow-up. Retention rate, reason for discontinuation and subsequent management data were collected at 6, 12, 18 months. Results: 220 patients (142 females, mean age 58+-7 years, disease duration 12+-4 years, ETN duration 7+-4 years) were enrolled, with median follow up of 12.1 (9.7-15.8) months duration; ETN was used in different biologic DMARDs treatment lines (first 76.8%, second 17.7%, third 3.2 %, fourth 2.3%). Study population was composed of 85 RA, 81 PsA, 33 AS, 14 JIA and 7 other conditions (mostly scleroderma). In the follow-up, 50 patients (22.7%) presented with at least one non-serious adverse event, with 36 (16, 4%) disease re-activation (mostly articular) and 30 (13, 6% - 11 for safety and 19 loss of efficacy) SB4 interruptions. Retention rates were 99.1 (210/212) at 6, 90.9% (150/165) at 12 and 81.5% (53/65) at 18 months respectively. Back-switch to ETN was performed in 17/30 cases, the remaining cases were managed with change of bDMARD or csDMARD). Age was the only significant predictor of SB4 interruption at 6 months (OR 1.058, 95%CI 1.007-1.112, p=0.026), while disease, bDMARD line, csDMARD combination, gender, disease duration or ETN duration did not influence retention rates at 6, 12 or 18 months. Conclusion: our real-life data confirm the safety profile of switching from ETN to SB4. In our patients, the data show a higher retention rate, when compared to other-real life registries data (1, 2) References: [1]Ebbers HC et al. Real-World evidence on Etanercept Biosimilar SB4 in Etanercept-Naïve or Switching Patients: A Systematic Review. Rheumatol Ther. 2019 Sep;6(3):317-338. Disclosure of Interests: Cosimo Bruni Speakers bureau: Actelion, Eli Lilly, Stefano Gentileschi: None declared, Marco Capassoni: None declared, Giovanni Pacini: None declared, Marco Bardelli: None declared, Caterina Baldi: None declared, Lorenzo Tofani: None declared, Laura Cometi: None declared, Francesca Nacci: None declared, Francesca Bartoli: None declared, Ginevra Fiori: None declared, Luca Cantarini: None declared, Serena Guiducci: None declared, Bruno Frediani: None declared, Marco Matucci-Cerinic Grant/research support from: Actelion, MSD, Bristol-Myers Squibb, Speakers bureau: Acetelion, Lilly, Boehringer Ingelheim